Functional aspects of strength training using Vascular Occlusion (International Seven Journal of Health Research, 2024)
The demand for weight training has grown widely in Brazil and around the world. This practice is used for various purposes, such as maintaining health, improving performance and aesthetic purposes, seeking to promote muscle improvement, increased strength, among other benefits. Strength training with vascular occlusion consists of using a flexible cuff on the muscles being worked at a low intensity, and can be aimed at different practitioners, from people undergoing rehabilitation to high-performance athletes. The aim of this study was to review the literature on strength training using vascular occlusion. This type of training has been offering excellent results for increasing muscle mass and strength, and can be applied to all types of bodybuilders, from young people to the elderly, and is recommended for people who are unable to reach high load levels. The use of low-intensity occlusion induces an improvement in muscle hypertrophy and an increase in strength in the flexor muscles, in general contributing to the professional and academic scenario on occlusive training and its practice.